God And Man In The Qur’an : Semantics Of The Qur’anic Weltanschaungg : Struktur Dasar Weltanschauung Al Quran Dan Ontologis Antara Tuhan Manusia - mayasari, lutfiana dwi; azizah, aisyatul; Aprilia, Amanda Carolina dara (Fakta: Forum Aktual Ahwal Al-Syakhsiyah, 2023)
The Qur'an is a holy book that was revealed directly by Allah to humans through His messenger, the Prophet Muhammad. Understanding the Qur'an which was directly revealed by the Creator makes humans also demand an understanding of how the position of humans with God is, it doesn't stop there, this will continue with widespread understanding and thinking about the concepts of life that humans want to understand completely. So that it is necessary to understand both the position of humans and God in order to find a good and correct understanding of what God means in the Qur'an as a provision for humans to complete their duties in the world, then try to discuss the Basic Structure of Weltanschauung Al-Quran and the Ontology Between God and Humans. The Quran explains that there is a relationship between man and God. The relationship between God and man can be in the form of ontological relations, communication relations, master and servant and ethical relations which in some of these relationships need to be related to one another. This perfect relationship then makes a certain group, the group is called the Muslim community. The Qur'an explains that the position of the Qur'an is to mediate between this world and the hereafter, where the Qur'an acts as a liaison or something that represents the transition between the two (world and the hereafter).